Most frequent diseases treated with medicinal plants by the inhabitant of the andean community of Huamachuco, Sanchez Carrion, La Libertad-Peru - Castillo Zavala, José Luis (2023)
It is indisputable the cultural and ancestral value acquired and deposited in the Andean-Amazonian Communities, on the correct use of medicinal plants; the same that unfortunately today is in danger of disappearing due to globalization. In this sense, the research sought to determine the most frequent diseases treated with medicinal plants by the population of Huamachuco, Sanchez Carrion, La Libertad, Peru. For this purpose, a total of 96 interviews were carried out, using the random sample selection method, taking into account that the inclusion criteria were met at all times. Likewise, the amount of population to be interviewed was chosen, and to obtain: the amount (%) of the inhabitants that use medicinal plants, as well as the types of diseases and/or ailments that burden the population. The results obtained showed that 90% of the population of Huamachuco uses medicinal plants and 10% does not use them. It is concluded that the most frequent diseases treated with medicinal plants are those related to the digestive and gastrointestinal systems, respiratory system and urinary system.